Integration of Religion and Science in Hossein Nassr's Perspective - Akhmad Mamba'ul Ulum; Amril M; Eva Dewi (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
The integration of religion and science has become the subject of interesting debate in the modern intellectual world. Hossein Nasr, an Islamic philosopher and scholar, made important contributions to understanding the relationship between these two fields. In his perspective, Nasr emphasizes the importance of understanding religion and science holistically, as two complementary dimensions in the search for truth. This article explores Nasr's thinking on the integration of religion and science, highlighting his arguments about the epistemological and ontological differences between the two as well as attempts to unite them in a coherent view. The discussion also includes the practical implications of Nasr's views in the context of modern life.